Health Expenditure, Health Outcomes and Economic Growth in Nigeria - Ogunjimi, Joshua Adeyemi; Adebayo, Adedeji Oluwatosin (Asian Journal of Economics and Empirical Research, 2019)
This study examined the relationship among health expenditure, health outcomes and economic growth in Nigeria for the period between 1981 and 2017. This study adopted the Toda-Yamamoto causality framework to examine these relationships. The Augmented Dickey Fuller unit root test was used to check for maximum order of integration of the variables used in the study and the result was one while the Autoregressive Distributed Lag (ARDL) Bounds test approach to cointegration was used to investigate if a long-run relationship exists among the macroeconomic variables used in the study and the result was in the affirmative. The results of the Toda-Yamamoto causality tests showed a unidirectional causality running from health expenditure to infant mortality while there is no causality between real GDP and infant mortality; a unidirectional causal relationship running from health expenditure and real GDP to life expectancy and maternal mortality; and a unidirectional causal relationship running from real GDP to health expenditure. This study therefore recommended that the Nigerian government should make concerted efforts geared towards increasing the health expenditure at least to meet up with the WHO’s recommendation that all countries should allocate at least 13 per cent of their annual budget to the health sector for effective funding as this would bring desired health outcomes and employ the use of modern technology and the services of professional health personnel should be sought to combat the high incidence of maternal and infant mortality in the health sector in Nigeria.